Predatory Journals on Trial: Allegations, Responses, and Lessons for Scholarly Publishing from FTC v. OMICS - Manley, Stewart (University of Toronto Press, 2019)
On 25 August 2016, the US Federal Trade Commission (FTC) sued OMICS Group Inc., iMedPub LLC, Conference Series LLC, and Srinubabu Gedela, all affiliated with open access mega-publisher OMICS International, for deception in their solicitation of journal articles and advertising of conferences. The ongoing lawsuit seeks to stop OMICS's deceptive practices and disgorge US $50.5 million in ill-gotten gains. OMICS has in turn claimed over $2.1 billion for harm caused by the lawsuit to its business and employees. This article describes the main arguments, counter-arguments, and court decisions in the 5920 pages of pleadings, exhibits, and orders that have been filed through 14 October 2018. The article then evaluates the case to formulate key take-aways for publishers, editors, academics, and universities. Depending on its ultimate outcome, the case against OMICS may be a turning point in the practices of questionable open access online publishers, making this interim case assessment pertinent to all concerned about the future of academic publishing. © University of Toronto Press.